The immune and metabolic treatment approach of using testosterone on mice models of liver injury - Amer, Johnny; Salhab, Ahmad; Snobar, Hadeel; Alhabil, Yazan (Frontiers in Pharmacology, 2023)
Background: Natural killer (NK) cells showed an anti-fibrotic effect; however, their function is thought to be impaired in advanced liver injury. In the current study, we aimed to assess the immune and metabolic impact of testosterone on mice models of liver injury. Methods: Carbon-tetrachloride induced liver fibrosis male mice models was i.p injected for 2 weeks (acute) and 4 weeks (chronic) (n = 36). Testosterone (4 mg/kg mouse body weight) was injected i.p. following the first week of the acute model of CCl4 and following the second week of the chronic model of CCl4. At the end of the experiments, mice were sacrificed, and serum was collected for assessing liver enzymes of ALT and AST, as well as inflammatory markers of IL-6, metabolic makers of C-peptide levels, and lipid and glucose profiles. Livers were harvested and used for histological assessments for inflammation and fibrosis. Fibrosis profiles from liver extracts, αSMA and Collagen III, were assessed by RT-PCR. Moreover, liver tissue-resident NK cells were isolated and evaluated for their activity by assessing INF-γ and IL-6 receptors using ELISA and flow cytometry, respectively. Results: Serum ALT, AST, and IL-6, as well as metabolic assessments of cholesterol, triglyceride, C-peptide, fasting blood sugar, and fibrotic profiles, were linearly correlated with disease progressions. Histological characterization of the liver was worsened in the chronic model of liver injury. Testosterone-treated mice exhibit a significant reduction in collagen depositions with less dense fibrosis tissue associated with reduced liver injury enzymes and metabolic markers in both the acute and chronic CCl4 mice models in favor of the latter one (p < 0.05). Moreover, testosterone treatments displayed a significant decrease in serum IL-6 of 2.4-fold (p = 0.0001) and 2.3-fold (p = 0.0003) in the acute and chronic models, respectively (p = 0.002), and data showed an increase in INF-γ release from NK associated with a reduction in their IL-6 receptor expressions (p < 0.05). Conclusion: Our results indicated effects of testosterone on mediating a decreased expressions of NK IL-6 receptors and consequently inducing their activation; which in part, could explain the amelioration of liver injury. Our data suggest an anti-inflammatory and anti-fibrotic treatment approach of using testosterone for delaying disease progressions.